Clinical-morphological and laboratory predictors of «superscan» scintigraphy phenomenon in prostate cancer - N. Yu. Shumilina; V. V. Vyazmin; E. Yu. Evdokimova; D. O. Dashanov; N. G. Chanchikova; R. A. Zukov (Сибирский онкологический журнал)
Introduction. Detection of bone metastases in cancer patients is of great importance in the choice of treatment tactics and assessment of the disease prognosis. The article discusses the «superscan» phenomenon on bone scintigraphy in detecting skeletal metastases in prostate cancer (PC) patients. When analyzing published reports, we found only one large prospective study and a few case report publications on the detection of «superscan» in patients with generalized skeletal involvement.The purpose of the study was to determine the laboratory and clinical morphological parameters associated with «superscan» scintigraphic phenomenon in patients with prostate cancer.Material and Methods. Of 2474 prostate cancer patients who underwent bone scintigraphy, 48 had the «superscan» phenomenon. Clinical, laboratory and morphological parameters were: age of the patients, tumor stage by TNM (7th edition, 2010), histological type of the tumor, Gleason index, prostate specific antigen (PSA) level, pain syndrome (on a 5-point verbal scale of pain estimates, 1982), the presence of castration-resistant prostate cancer, hemoglobin level and erythrocyte sedimentation rate (ESR).Results. The «superscan» phenomen was found to occur most often in prostate cancer patients aged 60-69 years. Stage III and IV tumors were detected in 97.9 % of cases, lymphatic invasion in 20.8 %, and visceral metastases in 12.5 %. In addition, the phenomenon was associated with high PSA levels (the mean PSA level was 100 ng/ml, range: 26-4957) and the presence of moderately and poorly differentiated (Gleason ≥7)) tumors. Chronic pain syndrome at the time of detection of «superscan» was observed in 47.9% of patients, castration resistance - in 16.6 %. The median hemoglobin level was 114 (75-139) g/l and ESR was 34 (14-62) mm/h.Conclusion. The most significant factors associated with the «superscan» scintigraphy phenomenon in prostate cancer patients were the primary tumor extension, high PSA level and low-grade tumors. New data on the association between the «superscan» phenomenon and the levels of hemoglobin and ESR have been obtained. Further studies on the relationship between the «superscan» phenomenon and pain syndrome and castration resistance are required.